2013
DOI: 10.1002/pssa.201329319
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of CuI films prepared by spin coating

Abstract: Thin films of cuprous iodide (CuI), which is expected to be used in solid-state dye-sensitized solar cells as a hole conductor, were formed by spin coating and subsequent annealing. The effects of the annealing conditions on the electrical properties of the CuI films were investigated by resistivity and Hall-effect measurements. The CuI films showed p-type conduction with resistivities of 0.3-5 V cm, carrier concentrations of 1 Â 10 18 -1 Â 10 19 cm À3 and mobilities of 0.5-2 cm 2 V À1 s À1.It was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 19 publications
2
57
0
1
Order By: Relevance
“…CuI has large band gap (3.1 eV), high hole mobility (0.2–2 cm 2 V −1 s −1 ), good chemical stability and low production cost . These unique properties make CuI as an excellent choice as a hole conductor.…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…CuI has large band gap (3.1 eV), high hole mobility (0.2–2 cm 2 V −1 s −1 ), good chemical stability and low production cost . These unique properties make CuI as an excellent choice as a hole conductor.…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…It has been reported that the Cu vacancy (V Cu ) in CuI plays the role of the dominant native acceptor [28]. The evaporation of a trace amount of iodine from a CuI film that decreased the concentration of V Cu , and the hole concentration decreased accordingly [10]. The hole mobility exhibits similar temperaturedependent behaviour to the carrier concentration.…”
mentioning
confidence: 94%
“…Zhu et al reported that CuI thin films grown with a pulse laser deposition (PLD) technique exhibiting the resistivity of 0.1–1 Ωcm and a transmittance of about 60–80% in the 410–1000 nm range . Inudo et al reported CuI films formed by spin coating and subsequent annealing with typical resistivity of 0.3–5 Ωcm and mobility of 0.5–2 cm 2 V −1 s −1 . Compared with these reports, Tanaka et al obtained CuI films by vacuum evaporation techniques with the same transmittance as RF‐DC coupled magnetron sputtering, while the reported resistivity was 10 −2 Ωcm .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the resistivity of the film would increase with the I/Cu ratio. Inudo et al [11] had studied the electrical properties of the air or Ar annealed CuI films fabricated by spin coating. The prepared film showed a high hole concentration of 1 9 10 18 -1 9 10 19 cm -3 .…”
Section: Introductionmentioning
confidence: 99%